2004
DOI: 10.1180/0009855043910123
|View full text |Cite
|
Sign up to set email alerts
|

Smectite in Spodosols from the Adirondack Mountains of New York

Abstract: A B S T R A C T : Clay mineral analysis of Spodosols collected from the Adirondack Mountains reveals that smectite is common in the forest floor and uppermost soil horizons (the O, A and E horizons) and probably forms from the transformation of vermiculite via a low-charge vermiculite intermediate. The conversion of vermiculite to smectite occurs in the upper part of the soil profile where organic acids and strong inorganic acids (derived from atmospheric deposition) combine to create an intense weathering env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…humus) bound with the increasing amounts of Fe and Al was transported with depth until the complex becomes insoluble and sorbs. April et al (2004) reported soil solutions draining the O horizon showed elevated fluxes and concentrations of organic and particulate Al, while concentrations and fluxes of inorganic monomeric Al were low. It seems likely that Al is largely mobilized from the forest floor by organic acid dissolution of soil minerals.…”
Section: Correlations Between Amount Of Al- Fe-and Mn-pools and Soilmentioning
confidence: 99%
“…humus) bound with the increasing amounts of Fe and Al was transported with depth until the complex becomes insoluble and sorbs. April et al (2004) reported soil solutions draining the O horizon showed elevated fluxes and concentrations of organic and particulate Al, while concentrations and fluxes of inorganic monomeric Al were low. It seems likely that Al is largely mobilized from the forest floor by organic acid dissolution of soil minerals.…”
Section: Correlations Between Amount Of Al- Fe-and Mn-pools and Soilmentioning
confidence: 99%
“…It is therefore not surprising that as fluids continued to access the biotite structure, loss of K mass persisted, and ultimately resulted in small amounts of kaolinite forming at this site. Such reactions between downward migrating solutions and biotite are well documented in the literature (April et al, 1986;April et al, 2004;Aspandiar and Eggleton, 2006;Bisdom et al, 1982;Harraz and Hamdy, 2010;Jolicoeur et al, 2000;Nettleton et al, 1970;Wilson, 2004). However, the interplay between fluids and the base silicate framework did not produce a statistically significant change in bulk mass (Table 5).…”
Section: Zr IImentioning
confidence: 58%
“…However, as shown below the resulting estimates of elemental and bulk mass change produce a coherent picture of regolith development that is consistent with existing petrologic and clay mineralogic data and our knowledge of common fluid-rock interactions (e.g., Nettleton et al, 1970;Nesbitt, 1979;Nesbitt andYoung, 1984, 1989;Nesbitt and Markovics, 1997;White et al, 2001;Graham et al, 2010;Girty et al, 2014;Parizek and Girty, 2014). For instance, the transformation of biotite to vermiculite is widely recognized as a common alteration process occurring within the regolith, as is the translocation of clay particles (April et al, 1986;April et al, 2004;Aspandiar and Eggleton, 2006;Bisdom et al, 1982;Harraz and Hamdy, 2010;Jolicoeur et al, 2000;Nettleton et al, 1970;Wilson, 2004). Hence, our expectation is that mass balance calculations utilizing the selected framework elements will indicate that K mass has been lost from ZR I and ZR II, while the translocation of kaolinite (Al 2 Si 2 O 5 (OH) 4 ) into the saprock system at ZR III should have introduced an increase in Si and Al mass.…”
Section: Identifying a Reference Frame And Calculating Elemental And mentioning
confidence: 64%
“…Vermiculite possibly converts to smectite under acidic conditions (April et al, 2004). The dominance of smectite in the Ah-horizons closest to kauri at location 6 SP1 and the presence of small amounts of smectite in all horizons at location 5 indicate that vermiculite may also be converted to smectite under the acidic conditions encountered under kauri.…”
Section: Discussionmentioning
confidence: 98%